2018
DOI: 10.1016/s1470-2045(18)30487-x
|View full text |Cite
|
Sign up to set email alerts
|

Pazopanib in patients with von Hippel-Lindau disease: a single-arm, single-centre, phase 2 trial

Abstract: Novartis Inc and NIH National Cancer Institute core grant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
54
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 29 publications
1
54
1
Order By: Relevance
“…Thus far, therapeutic options for VHL patients are only derived from surgery and, unfortunately, the preoperative neurological deficits do not resolve after surgery 12 . In addition, the systemic therapies, mainly antiangiogenic, used for metastatic cancers had shown limited response in VHL tumours 13,14 . Therefore, and due to the lack of effective therapies for diffuse or recurrent disease, there is an urgent demand for effective drugs for VHL patients, especially those medicines that might halt the progression of tumours and subsequently delay surgical treatment.…”
mentioning
confidence: 99%
“…Thus far, therapeutic options for VHL patients are only derived from surgery and, unfortunately, the preoperative neurological deficits do not resolve after surgery 12 . In addition, the systemic therapies, mainly antiangiogenic, used for metastatic cancers had shown limited response in VHL tumours 13,14 . Therefore, and due to the lack of effective therapies for diffuse or recurrent disease, there is an urgent demand for effective drugs for VHL patients, especially those medicines that might halt the progression of tumours and subsequently delay surgical treatment.…”
mentioning
confidence: 99%
“…Of the 45 patients in whom disease progressed while on first line treatment, 10 (22%) demonstrated response with a disease control rate of 75% [30]. More recently, Jonasch et al demonstrated in a Phase II, single center trial that patients with diagnosed vHL may see response to tumors of multiple organs when started on pazopanib therapy [31]. Of the 31 patients treated with pazopanib, 13 (42%) demonstrated objective response with the most pronounced effect in pancreatic lesions (9 of 17, 53%) and renal cell carcinomas (31 of 59, 52%); only 2 of 49 (4%) CNS hemangioblastomas demonstrated objective response [31].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Jonasch et al demonstrated in a Phase II, single center trial that patients with diagnosed vHL may see response to tumors of multiple organs when started on pazopanib therapy [31]. Of the 31 patients treated with pazopanib, 13 (42%) demonstrated objective response with the most pronounced effect in pancreatic lesions (9 of 17, 53%) and renal cell carcinomas (31 of 59, 52%); only 2 of 49 (4%) CNS hemangioblastomas demonstrated objective response [31]. These trials illustrate the treatment potential of pazopanib in patients with various tumor types, including those often associated with vHL.…”
Section: Discussionmentioning
confidence: 99%
“…An important study published in The Lancet investigated the efficacy of pazopanib in 31 patients with VHL and reported an objective response in 13 patients (42%). However, treatment-related serious adverse events included one case each of appendicitis and gastritis, and one patient had a fatal central nervous system bleeding 21 .…”
Section: Discussionmentioning
confidence: 99%